Acute Toxicity and Genotoxic Activity of Avocado Seed Extract (Persea americana Mill., c.v. Hass) - Eduardo Padilla-Camberos; Moisés Martínez-Velázquez; José Miguel Flores-Fernández; Socorro Villanueva-Rodríguez (The Scientific World Journal)
The use of vegetal extracts requires toxicological and genotoxic evaluations to establish and verify safety before being added to human cosmetic, pharmaceutical medicine, or alimentary products. Persea americana seeds have been used in traditional medicine as treatment for several diseases. In this work, the ethanolic seed extract of Persea americana was evaluated with respect to its genotoxic potential through micronucleus assay in rodents. The frequency of micronuclei in groups of animals treated with avocado seed extract showed no differences compared to the negative control (vehicle); therefore, it is considered that the avocado seed extract showed no genotoxic activity in the micronucleus test.